Pengaruh Likuiditas, Leverage, dan Ukuran Perusahaan terhadap Profitabilitas pada Perusahaan Transportasi yang Tedaftar di BEI Periode 2021-2024 - Ayu Khoirun Nisa; Arda Raditya Tantra (AKUNTANSI 45, 2026)
The transportation sector is one of the strategic industries that supports national economic growth. Due to its high operational costs and large investment needs, profitability is an important indicator in assessing company performance. Liquidity, leverage, and firm size are considered internal factors that may influence a company’s ability to generate profits, especially in the post-pandemic period. This study aims to examine the effect of liquidity, leverage, and firm size on profitability in transportation companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The research used a quantitative approach with secondary data obtained from company financial statements. Samples were selected using purposive sampling, resulting in 92 research samples. Data analysis was conducted using multiple linear regression with SPSS software. The findings show that liquidity has a positive and significant effect on profitability, leverage has a positive but insignificant effect, and firm size has a negative and significant effect on profitability. Simultaneously, all independent variables significantly influence profitability, with an F-value of 9.029 and a significance level of 0.000. The coefficient of determination (R²) value of 0.235 indicates that 23.5% of profitability variation can be explained by the three variables, while the remaining 76.5% is influenced by other factors outside the research model.